Characterization of the prevalence of excess weight in Brazil - Marcia Domênica Cunico Barancelli; Marcio Gazolla; Sergio Schneider (BMC, 2022)
Abstract Introduction/Background This work aims to analyse the prevalence of excess weight in Brazil to demonstrate the nutritional transition that is occurring. The data mobilized in the research are from the Food and Nutritional Surveillance System (FNSS). Materials and methods This study employed a quantitative approach from the FNSS online secondary data survey through reports of nutritional status in different phases of life (child, adolescent, adult, elderly and pregnant), in different macroregions of the country (South, Southeast, Midwest, Northeast and North) and with a 12-year historical series (2008 to 2019). Results In the adult life stage, there was a time trend of increasing excess weight in all regions of this historical series. The southern region of Brazil and the adult life stage had the highest national percentage of excess weight (69,1%) in 2019 and had the lowest percentage of eutrophy (29.3%) in the region in 2019. In the elderly life phase, in the South, Southeast and Midwest regions, excess weight was higher than the other outcomes in the time series, with the highest annual prevalence in the South region (58,6%) in 2019. In the adolescent life stage, there was a time trend of increasing excess weight in all regions, and excess weight had the highest prevalence in 2019 in the South (35,8%). The lowest prevalence rates of excess weight were in the following age groups: children aged 0 to <  2 years old and children aged 2 to <  5 years old. Additionally, it was in Group 5 to < 10 years old that the most critical prevalence of excess weight (35,07%) was found in 2018. However, malnutrition (low weight) persists, especially in the elderly and children. In the pregnancy life stage, there was a temporal trend of increase in excess weight in all regions, with higher percentages in 2019 in the South (53.5%) and Southeast (50.8%). Conclusion Excess weight has shown increasing time trends in the adolescent, adult, elderly and pregnant life stages in all regions of Brazil, suggesting that public FNS policymakers should be more assertive in the planning and management of programs and actions to reduce the percentages of diseases.